Strontium-doping promotes bone bonding of titanium implants in osteoporotic microenvironment - Geng, Tengyu; Wang, Yiru; Lin, Kaili; Zhang, Cheng; Wang, Jing; Liu, Ya; Yuan, Changyong; Wang, Penglai (Frontiers in Bioengineering and Biotechnology, 2022)
Osteoporosis is a major challenge to oral implants, and this study focused on improving the osseointegration ability of titanium (Ti) implants in osteoporosis environment via surface modification, including doping of strontium ion and preparation of nanoscale surface feature. Our previous studies have shown that strontium (Sr) ions can enhance osteogenic activity. Therefore, we aimed to comprehensively evaluate the effect of hydrothermal treatment of Sr-doped titanium implant coating on bone-binding properties in the microenvironment of osteoporosis in this study. We fabricated Sr-doped nanocoating (AHT-Sr) onto the surface of titanium implants via hydrothermal reaction. The rough Sr-doping had good biological functions and could apparently promote osteogenic differentiation of osteoporotic bone marrow mesenchymal stem cells (OVX-BMSCs). Most importantly, AHT-Sr significantly promoted bone integration in the osteoporosis environment. This study provides an effective approach to implant surface modification for better osseointegration in an osteoporotic environment.